Designing for growth : a design thinking tool kit for managers - Liedtka, Jeanne; Ogilvie, Tim. (New york : Columbia University Press, 2011)
Jeanne Liedtka and Tim Ogilvie educate readers in one of the hottest trends in business: "design thinking," or the ability to turn abstract ideas into practical applications for maximal business growth. Liedtka and Ogilvie cover the mind-set, techniques, and vocabulary of design thinking, unpack the mysterious connection between design and growth, and teach managers in a straightforward way how to exploit design's exciting potential. Exemplified by Apple and the success of its elegant products and cultivated by high-profile design firms such as IDEO, design thinking unlocks creative right-brain capabilities to solve a range of problems. This approach has become a necessary component of successful business practice, helping managers turn abstract concepts into everyday tools that grow business while minimizing risk.
Keywords: Creative ability in business; Organizational change; Success in business